Dietary Supplementation With the Ketogenic Diet Metabolite Beta-Hydroxybutyrate Ameliorates Post-TBI Aggression in Young-Adult Male Drosophila - Lee, Derek C.; Vali, Krishna; Baldwin, Shane R.; Divino, Jeffrey N.; Feliciano, Justin L.; Fequiere, Jesus R.; Fernandez, Mirella A.; Frageau, James C.; Longo, Frank K.; Madhoun, Salaheddine S.; Mingione V, Pasquale; O’Toole, Timothy R.; et al. (Frontiers in Neuroscience, 2019)
Traumatic brain injury (TBI), caused by repeated concussive head trauma can induce chronic traumatic encephalopathy (CTE), a neurodegenerative disease featuring behavioral symptoms ranging from cognitive deficits to elevated aggression. In a Drosophila model, we used a high-impact trauma device [Katzenberger et al., 2013, 2015] to induce TBI-like symptoms and to study post-TBI behavioral outcomes. Following TBI, aggression in banged male flies was significantly elevated as compared with that in unbanged flies. These increases in aggressive behavior were not the result of basal motility changes, as measured by a negative geotaxis assay. In addition, the increase in post-TBI aggression appeared to be specific to concussive trauma: neither cold exposure nor electric shock—two alternate types of trauma—significantly elevated aggressive behavior in male-male pairs. Various forms of dietary therapy, especially the ketogenic diet (KD), have recently been explored for a wide variety of neuropathies. We thus hypothesized that putatively-neuroprotective dietary interventions might be able to suppress post-traumatic elevations in aggressive behavior in animals subjected to head- trauma-inducing strikes, or “bangs”. We supplemented a normal high-carbohydrate Drosophila diet with the KD metabolite beta-hydroxybutyrate (-HB)—a ketone body (KB). Banged flies raised on a KB-supplemented diet exhibited a marked reduction in aggression, whereas aggression in unbanged flies was equivalent whether dieted with KB supplements or not. Pharmacological blockade of the ATP-sensitive potassium (KATP) channel abrogated KB effects reducing post-TBI aggression while pharmacological activation mimicked them, suggesting a mechanism by which KBs act in this model. KBs did not significantly extend lifespan in banged flies, but markedly extended lifespan in unbanged flies. We have thus developed a functional model for the study of post-TBI elevations of aggression. Further, we conclude that dietary interventions may be a fruitful avenue for further exploration of treatments for TBI- and CTE-related cognitive-behavioral symptoms.